Looking back : Davis Grocery (Raton, NM Raton Range, 1978)
Article reads: A grocer, dressed in white, and a bearded gentleman, dressed in somber back, posed for this 1917 photo of Davis Grocery in Raton, This old photograph was submitted to the Range's "Looking Back" series by Mrs. Cecil Decker of 526 Cook Avenue.
Master list item #: 86
File location is in the Raton file Cabinet
Newspaper article + Photograph of Inside the Davis Grocery Store in 1917
Keywords: Decker, Cecil Mrs; Davis Grocery; Business History; Local Business; Grocery Stores; 526 Cook Avenue -- Raton, New Mexico